Cellular Uptake and Intracellular Trafficking of Oligonucleotides: Implications for Oligonucleotide Pharmacology - Juliano, R.L. (Mary Ann Liebert, Inc., 2014)
One of the major constraints on the therapeutic use of oligonucleotides is inefficient delivery to their sites of action in the cytosol or nucleus. Recently it has become evident that the pathways of cellular uptake and intracellular trafficking of oligonucleotides can strongly influence their pharmacological actions. Here we provide background information on the basic processes of endocytosis and trafficking and then review recent literature on targeted delivery and subcellular trafficking of oligonucleotides in that context. A variety of approaches including molecular scale ligand-oligonucleotide conjugates, ligand-targeted nanocarriers, and the use of small molecules to enhance oligonucleotide effects are discussed.